2008
DOI: 10.1083/jcb.200712154
|View full text |Cite
|
Sign up to set email alerts
|

Glial and neuronal isoforms of Neurofascin have distinct roles in the assembly of nodes of Ranvier in the central nervous system

Abstract: Rapid nerve impulse conduction in myelinated axons requires the concentration of voltage-gated sodium channels at nodes of Ranvier. Myelin-forming oligodendrocytes in the central nervous system (CNS) induce the clustering of sodium channels into nodal complexes flanked by paranodal axoglial junctions. However, the molecular mechanisms for nodal complex assembly in the CNS are unknown. Two isoforms of Neurofascin, neuronal Nfasc186 and glial Nfasc155, are components of the nodal and paranodal complexes, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
254
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(277 citation statements)
references
References 51 publications
17
254
2
4
Order By: Relevance
“…Two particularly interesting examples include the differential expression of neuronal and glial isoforms of Nfasc and Sgce genes (Zonta et al, 2008;Ritz et al, 2011), both of which are confirmed in our splicing database, among others. Next, to validate the accuracy of the novel cell type-specific splicing events in our dataset, we searched for a biologically significant gene candidate to validate via PCR.…”
Section: An Alternative Splicing Database Of Glia Neurons and Vascusupporting
confidence: 68%
“…Two particularly interesting examples include the differential expression of neuronal and glial isoforms of Nfasc and Sgce genes (Zonta et al, 2008;Ritz et al, 2011), both of which are confirmed in our splicing database, among others. Next, to validate the accuracy of the novel cell type-specific splicing events in our dataset, we searched for a biologically significant gene candidate to validate via PCR.…”
Section: An Alternative Splicing Database Of Glia Neurons and Vascusupporting
confidence: 68%
“…Our data do not allow us to distinguish whether Sh3tc2 is directly involved in the formation and/or maintenance of the node of Ranvier or whether the observed nodal widening is a secondary effect of hypomyelination. However, previous data show that disruption of the nodal gene Nfasc in the CNS results in a reduction of myelination, suggesting that the nodal phenotype could be the primary defect also in CMT4C (24). Moreover, our transcriptomic analysis revealed a 4-fold increase of expression of the nodal matrix gene Hapln2 already in 1-month-old Sh3tc2 ⌬Ex1/⌬Ex1 mice (Table S1), suggestive of the presence of early modifications in the nodal environment (25).…”
Section: Discussionmentioning
confidence: 52%
“…30). In addition, other mechanisms participate in node assembly, including glial-derived extracellular matrix-mediated clustering of NF186, restriction of nodal protein mobility through a paranodal barrier, and stabilization of nodal proteins through interactions with the cytoskeleton (52,53).…”
Section: Resultsmentioning
confidence: 99%